Comprehensive thermal and structural characterization of antimony-phosphate glass - S.Y. Moustafa; M.R. Sahar; S.K. Ghoshal (Results in Physics, 2017)
For the first time, we prepare new ternary glass systems of composition (95-x)Sb2O3-xP2O5-5MgO, where x = 45, 40, 35 mol%; (85-x)Sb2O3-xP2O5-15MgO, where x = 55, 35, 25 mol%; (75-x)Sb2O3-xP2O5-25MgO, where x = 45, 35, 25 mol%; and 60Sb2O3-(40-x)P2O5-xMgO, where x = 10, 20 mol% via melt-quenching method. Synthesized glasses are characterized using XRD, FESEM, EDX, and TG/DTA measurements. The influence of varying modifier concentrations on their thermal properties is evaluated. The XRD patterns confirmed the amorphous nature of samples. SEM images demonstrated interesting phase formation with ribbons-like texture. Five crystalline phases are evidenced in the ternary diagram which are antimony phosphate and antimony orthophosphate as major phases as well as magnesium phosphate, magnesium cyclo-tetraphosphate and cervantite as minor phases. EDX spectra detected the right elemental traces. Detailed thermal analysis of these glasses revealed their high-molecular polymer character for Sb2O3 content greater than 50 mol%. Three different glass transition temperatures are achieved around 276, 380–381 and 422–470 °C depending on the composition. Furthermore, the solidus and liquidus temperature are found to decrease with increasing Sb2O3 and increases for MgO contents till 15 mol% and then decrease, where the lowest recorded solidus temperature is 426 °C. This observation may open up new research avenues for antimony based ternary glasses and an exploitation of the derived results for optoelectronics applications, photonic devices and non-linear optical devices. Keywords: Antimony-phosphate glass, Thermal properties, Solidus temperature, Liquidus temperature, Crystalline phases